The Rise of Wage Theft Laws: Can Community–Labor Coalitions Win Victories in State Houses?. (September 2016) - Doussard, Marc; Gamal, Ahmad
Seeking regulatory power unavailable at the urban scale, community–labor coalitions have persuaded dozens of state legislatures to enact legislation addressing the problem of wage theft in low-wage service industries. The project of wage theft reform raises important questions about whether urban coalitions can effectively pursue their advocacy goals in State Houses. Drawing on an inventory of 255 wage theft laws proposed between 2004 and 2012, we evaluate three rival explanations of why wage theft legislation succeeds: worker grievances, political conditions, and movement strength. We find that states with larger numbers of worker centers and higher union density are more likely to both propose and enact wage theft legislation. Our results also suggest that urban reform movements maintain greater power to set legislative agendas than they do to ensure the passage of proposed laws. This suggest that "new labor" actors have developed state-level political power that warrants further scrutiny and explanation.